TRANSFORMATION OF NOMADIC EXISTENCE (Journal of Philosophy, Culture and Political Science, 2021)
Annotation. When conducting a study of the national mentality of Kazakhstan, it became necessary to analyze the transformation of the society of the Kazakh people since the formation of the Kazakh Khanate and the modern, independent Republic of Kazakhstan. The determination is made on the basis of the perception of information from the surrounding reality by society. This is the division into auditory and visual (oculocentrism) culture of the Kazakh society. This is confirmed by changes in all forms of culture.The world-setting of the Kazakhs is aimed at contemplating nature, the surrounding reality without changing it, but living with it in complete harmony, respecting and preserving natural resources. Cattle breeding was the main source of livelihood. However, there is a noticeable respect for the animal. We know everything about the culture of Kazakhs from oral folk art. Associations arise primarily related to the nomadic way of life, in unconditional creation of libraries, somehow fixing knowledge. Reflecting on this, there is a need for a return, to the determination of the Turkic culture, to the late and modern, the need to speak about the principle of this division. It should be noted that Kazakh culture, as is clear, did not survive these stages in an instant. This process took place gradually, settling on the subconscious side of the human mind. Listening to being by the Turkic nomads opens before us a whole world full of features associated with the perception of reality, and its no less interesting embodiment in folklore.Key words: oculocentrism, transformations, mentality, visual culture, nomadism, determination.